N‐Glycan‐based ER Molecular Chaperone and Protein Quality Control System: The Calnexin Binding Cycle. (10th January 2016) - Lamriben, Lydia; Graham, Jill B.; Adams, Benjamin M.; Hebert, Daniel N.
Abstract : Helenius and colleagues proposed over 20‐years ago a paradigm‐shifting model for how chaperone binding in the endoplasmic reticulum was mediated and controlled for a new type of molecular chaperone‐ the carbohydrate‐binding chaperones, calnexin and calreticulin. While the originally established basics for this lectin chaperone binding cycle holds true today, there has been a number of important advances that have expanded our understanding of its mechanisms of action, role in protein homeostasis, and its connection to disease states that are highlighted in this review. Abstract : Over two‐decades ago, Ari Helenius proposed a model that described a novel molecular chaperone binding cycle that was controlled by the composition of the N‐linked glycans on the substrates. This review highlights the recent advances in our understanding of the molecular mechanism, role in protein homeostasis and links to disease states for the endoplasmic reticulum carbohydrate‐binding chaperones, calnexin and calreticulin.